Determinants of Cross-Sectional and Longitudinal Health-Related Quality of Life in Memory Clinic Patients Without Dementia. (September 2020) - Banning, Leonie C. P.; Janssen, Eveline P. C. J.; Hamel, Renske E. G.; de Vugt, Marjolein; Köhler, Sebastian; Wolfs, Claire A. G.; Oosterveld, Saskia M.; Melis, Rene J. F.; Olde Rikkert, Marcel G. M.; Kessels, Roy P. C.; Pijnenburg, Yolande A. L.; Koene, Ted; et al.
Objective: To identify determinants within 3 different domains (ie, somatic comorbidities, cognitive functioning, and neuropsychiatric symptoms [NPS]) of health-related quality of life (HRQoL) over time in memory clinic patients without dementia. Methods: This longitudinal multicenter cohort study with a 3-year observation period recruited 315 individuals (age: 69.8 ± 8.6, 64.4% males, Mini-Mental State Examination score 26.9 ± 2.6). A multivariable explanatory model was built using linear mixed effects models (forward selection per domain) to select determinants for self-perceived HRQoL over time, as measured by the EuroQoL-5D visual analogue scale (EQ VAS). Results: Mean HRQoL at study entry was 69.4 ± 15.6. The presence of agitation, appetite and eating abnormalities, and eyes/ears/nose (ie, sensory impairment) comorbidities were associated with a change in HRQoL over time. Agitation was most strongly associated with HRQoL over time. Conclusions: The association of somatic comorbidities and NPS in memory clinic patients with course of HRQoL shows that these should receive more awareness, detection, and monitoring by clinicians.